Analytical Analysis of the Interfacial Stress in Damaged Reinforced Concrete Beams Strengthened by Bonded Composite Plates - Hassaine Daouadji, T. (Проблемы прочности, 2013)
A theoretical method to predict the interfacial stresses in the adhesive layer of damaged reinforced concrete beams strengthened with externally bonded carbon fiber-reinforced polymer plate is presented. The adopted model is developed including the adherend shear deformations by assuming a linear shear stress through the depth of the reinforced concrete beam, while all existing solutions neglect this effect. In addition, in the present study the anisotropic damage model is adopted to describe the damage of the reinforced concrete beams. It is shown that the damage has a significant effect on the interfacial stresses in fiber-reinforced polymer damaged reinforced concrete beam.